eRME - Rapid Maxillary Expansion in the economic way - Sonali Mahadevia; Nozar Daruwala; Krishnamurthy; Malay Vaghamshi (Wolters Kluwer Medknow Publications, 2011)
Aim and Objectives: Rapid Maxillary Expansion constitutes a routine clinical procedure in orthodontics, involving separation of mid-palatine suture which is usually done with help of the Hyrax screw. However, because of its high cost, the use has been limited, especially in institutions. So, the purpose of this study was to construct an economical device which can expand the maxillary arch in growing patients. Materials and Methods: Six patients having constricted maxilla and posterior skeletal crossbite were randomly selected from the Department of Orthodontics. A unique, easy and simple alternative device for expanding the maxillary arch called economic Rapid Maxillary Expander (eRME) has been fabricated at about one-tenth the cost of the conventional Hyrax. Pre- and post-treatment effects were statistically tested by using paired t-test at 0.05 level of significance. Results and Conclusion: The study results showed an average expansion in canine, premolar and molar regions of 4.4 mm, 6.8 mm and 9.4 mm, respectively, having significant difference pre-and post-treatment. Thus, it shows that maxillary expansion is efficiently possible with the application of this newly constructed device named eRME. This appliance also acts as a fixed retainer to avoid relapse, hence negating the need for a separate retainer.